Propofol Injection Pain: Comparison of Large Antecubital Vein Versus Small Vein on Dorsum of Hand - Zahid Aziz Soomro, Tahir Ali, Syed Farjad Sultan, Ashok Perchani, Muhammad Arsalan Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effectiveness of large antecubital vein versus small vein on dorsum of hand in prevention of propofol injection pain in patients undergoing surgery in general anaesthesia.. Design of the Study: The study design was randomized control trial. Study Settings: Study was conducted at Department of Anesthesia, Dow University of Health sciences, Civil Hospital, Karachi from 23-05-18 till 23-11-18. Material and Methods: After obtaining a patient’s permission, data was gathered in the future. A total of 76 patients were studied (38 in group A and 38 in group B). Mean and standard deviation were used to represent demographic data, whereas frequency or percentages were used to represent the qualitative factors. As part of the post-segregation chi square test, which was applied to the data, the significance level was set at 0.01. Results of the Study:. A total of 76 patients were enrolled in the study (38 in each of the two groups). The average age in groups A and B was 39.25 ±3.91 and 38.71 ±4.01, respectively. The efficiency of the large antecubital vein vs the small vein on the dorsum of the hand in preventing propofol injection was 81.6 percent vs. 36.87 percent out of 38 patients in groups A and B. Conclusion: Using a large antecubital vein for propofol injection was found to be more effective than a small vein on the dorsum of the hand for preventing pain.